THE EFFECT OF USING WORDLESS PICTURE ON THE SECOND YEAR STUDENTS ABILIY OF SMPN 14 PEKANBARU IN WRITING NARRATIVE TEXT - Adriansyah, Heru; Delfi, Syofia; ', Marzuki (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The objective of this research was to find out whether there is a significant effect of using wordless picture on the second year students’ ability of SMPN 14 Pekanbaru in writing narrative texts.This research is a pre-experimental research using one group pre-test post-test design. In conducting this research, a single group without control group was selected to be a sample. There were 31 students were selected as the sample by using cluster random sampling. A writing test was used both in pre and post-test. T-test formula was used in order to find out the difference between pre-test and post-test and to analyze the hypotheses. After analyzing the data, it was found that t-test score was 6.302 while t-table score in significance level 5% df= 29was 2.05. Since t-test was higher than t-table, it can be concluded that alternative hypothesis was accepted and null hypothesis was rejected. It can be further understood that “there is a significant effect of using wordless picture on the second year students’ ability of SMPN 14 Pekanbaru in writing narrative texts”. Based on the research findings, it is suggested that wordless picture can help the students to improve their writing ability especially in writing narrative text.Key Words: Effect,Wordless Picture, Writing Ability, Narrative Text